ChemInform Abstract: Stereoselective Synthesis of Tetrahydroindolizines Through the Catalytic Formation of Pyridinium Ylides from Diazo Compounds. Issue 35 (August 2016) - Day, Jonathan; McKeever‐Abbas, Ben; Dowden, James
Abstract: Iron(III) and copper(I) complexes catalyze multicomponent cycloaddition reactions between diazo compounds, pyridines, and electrophilic alkenes to provide alkaloid‐inspired tetrahydroindolizidines in a diastereoselective manner.